British and U.S. Left Realism: A Critical Comparison - DeKeseredy, Walter S. (International journal of offender therapy and comparative criminology, 1991)
Left realism has generated enormous interest and controversy in critical criminology over the past several years both in North America and in the United Kingdom. While there are important similarities between the writings from these countries, there are also some deep differences and divisions. This article provides some explication of these similarities and differences within a critical context